Exploring Governance Structures and Employment Access in Port Development - Sumarno, Dwi Agus; Salsabila, Lubna; Ardieansyah, Ardieansyah (Khazanah Sosial, 2026)
Port development projects are widely expected to generate employment opportunities for local communities, yet employment participation in infrastructure development is often shaped by the structure of governance relationships that organize recruitment, workforce preparation, and institutional coordination. This study aims to examine the relationship between collaborative governance arrangements and employment access within a port development system using the collaborative governance framework of Ansell and Gash as the analytical lens. The research adopts a qualitative governance approach with a case study design to analyze institutional relationships and workforce participation mechanisms in port development. Data were collected through interviews, field observations, and document analysis involving stakeholders responsible for governance coordination and employment management. Data analysis was conducted using thematic coding techniques in NVivo 15, including open coding and axial coding, followed by cluster similarity analysis to identify relationships among governance dimensions. Network analysis was subsequently performed using Gephi 0.10.1 to visualize the correlation among actors and the distribution of coordination roles within the governance system. Data validity was ensured through triangulation across interviews, observations, and institutional documents, as well as consistency checks in coding and network mapping procedures. The findings indicate that employment access is closely associated with structured governance relationships in which institutional coordination, workforce readiness, and recruitment procedures operate through formal administrative systems dominated by institutional actors. The study concludes that collaborative governance provides a coordinated mechanism for managing workforce participation in infrastructure development, yet variations in institutional connectivity and stakeholder participation may result in uneven employment access among local communities. This research contributes to the field of governance and infrastructure development by demonstrating how the integration of qualitative coding analysis and network-based visualization can be used to examine the relationship between governance structures and employment participation in large-scale development contexts.